Numerical Investigation on the Effects of Embedding PVC Pipes in Reinforced Concrete Beams. - Ampaire, Comboni (Kabale University, 2024)
This study focused on how embedded PVC pipes affected the way reinforced concrete (RC) beams behaved. One of the six 300x300x3500mm beams that were modeled in Abaqus was solid, and the other five (B-25.4mm, B-50.8mm, B-76.2mm, B-101.6E50mm, and B-127E100mm) had different pipe sizes and locations. The material properties both elastic and plastic were assigned to the models and also contained concrete damaged plasticity (CDP) material qualities to effectively forecast failure processes. A concentrated load of 500KN was loaded onto the modeled beams and treated as simply supported. In addition, meshing was finished, with reinforcing meshing with global mesh with a global size of 100mm and concrete elements assigned to element type C3D8R hexagonal elements. After the analysis was turned in, the results were compared to those of a solid beam, including stresses, strains, the load-deflection ductility index, and crack patterns. The results indicated that the stresses in the bottom reinforcement and concrete increased as the pipe size grew. Furthermore, the ductility index and loading capacity declined with changes in pipe placement and size. Therefore, the location and size of the pipe affect the strength, stiffness, and ductility of the reinforced concrete.